2018
DOI: 10.4102/ajod.v7i0.363
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic learners’ experiences with their peers and teachers in special and mainstream primary schools in North-West Province

Abstract: BackgroundInclusive education requires that the framework within which education is delivered should be broad enough to accommodate equally the needs and circumstances of every learner in the society. This includes learners with disabilities like dyslexia who have been excluded from the formal education system. This article reports the findings of a qualitative study that explored and described the dyslexic learners’ experiences with their peers and teachers in special and public schools in North-West Province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Buttressing these findings are the findings of similar studies across the globe. Leseyane et al (2018) revealed that teachers in public schools were not patient with dyslexic learners but used negative comments that embarrassed them and offered no extra attention to them. English language teachers lack sufficient knowledge on the learning difficulties of learners with dyslexia as well as the inclusive language teaching practices (Indrarathne, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buttressing these findings are the findings of similar studies across the globe. Leseyane et al (2018) revealed that teachers in public schools were not patient with dyslexic learners but used negative comments that embarrassed them and offered no extra attention to them. English language teachers lack sufficient knowledge on the learning difficulties of learners with dyslexia as well as the inclusive language teaching practices (Indrarathne, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The policy of inclusive education stipulates equal learning opportunities for every child to enable them to attain their education and career fulfillment (Ahmad et al, 2018). Inclusive education is the kind of education that accommodates the needs of every learner in the society equitably irrespective of the state of their mental health (Leseyane et al, 2018). However, some children experience specific learning difficulties such as dyslexia concerning learning and that makes it harder for them to learn (Ahmad et al, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools in the poorer socioeconomic and low-cost areas remain predominantly Black and under-resourced, and frequently still have under-trained teachers who were mostly trained during the apartheid era under the inferior Bantu education. As a consequence of teachers not being well equipped for inclusive teaching, the research done on learners with barriers to learning and their experiences in inclusive schools shows that learners feel that they are insufficiently supported, and that their learning needs are not being met (Bansilal et al, 2010;Leseyane et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by difficulties with accurate or fluent word recognition and by poor spelling and decoding abilities. These difficulties typically result from a deficit in the phonological component of language (Leseyane et al, 2018). Despite its ascertained neurobiological origin, there is broad literature on the links between specific learning disabilities and socio-emotional difficulties (Caroll&Iles, 2006;Wilson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%